A Relay of Joy: An Artist and a Geographer Reflect Upon Cybernetic Assemblies and an Embodied Media Geography of Spätkapitalismus - Travis, Charles; Long, Tim (My University, 2010)
Perhaps it was the emergence of global media geographies of Spätkapitalismus (Late Capitalism) which provoked Deleuze and Guattari in their collaborative text Anti- Oedipus: Capitalism and Schizophrenia (1983) to claim that ‘the schizophrenic voyage is the only kind there is.’ However with the proliferation of digital technology, it is now possible to explore the schizoid disassociation between modern and ‘hyperglobal’ conceptions of time and space in artistic and inventive manners. This paper will discuss in the context of current critical and geographical thought the performance of a cybernetic assembly A Relay of Joy. Utilizing the faculties of aurality and tactility for playing sounds in response to marks placed on a sheet of paper. The user rendered as a Beckettian figure is hooded, so the sound relays the location of the mark, assisting coordination. The intention is to draw a face through a process of mental mapping that emerges in response to sound rather than sight. The implications of this device are strange, as initially it is difficult to work out what is happening. Using the machine, the user is locked into a cybernetic assembly, or an “abstract machine.” Drawing upon Deleuze and Guattari's concept of the ‘abstract machine’ comprises further abstractions of the body as a fragmented form. The machine deals with the abstractions of sound, stripping out sight in an attempt to locate a face that's going to emerge from touch. The sense impressions are perverted: it's a deliberate ill effect that turns the machine, as the crisis of late capitalist modernity turns in the subject.
PUBLISHED
Keywords: Geography; Capitalism; Time